Correlation Studies on Pollen Attributes and Grain Yield under Drought Stress in a Wild Multiparental Population of Rice (Oryza sativa L.) - , Bhavyasree R K, John Joel A (Archives of Current Research International, 2024)
The drought stress at the reproductive stage is causing a drastic reduction in rice yield. This is mainly due to the failure of male gametogenesis or dysfunction of male gametophyte. The wild Oryza species found to have more alleles contributing to drought tolerance and can be integrated to cultivated species. So, in this investigation, the change in pollen parameters with response to drought in the reproductive stage was studied in a wild introgressed multiparental population. The genotypes like WRM 27-48-4, WRM 74-9-4 and WRM 107-21-2 were identified from the population with minimum yield loss also had less reduction in the pollen parameters. The mean reduction in the yield of these genotypes was less than the cultivated Asian parent, which is drought susceptible. The correlation studies revealed that the pollen parameters are significantly and directly contributing to the seed yield under drought conditions. This suggests that the selection based on these characters will help to identify the genotypes which can reduce the yield loss due to reproductive stress.